2014
DOI: 10.4103/2277-9175.129371
|View full text |Cite
|
Sign up to set email alerts
|

Potent health effects of pomegranate

Abstract: Accumulating data clearly claimed that Punica granatum L. (pomegranate) has several health benefits. Pomegranates can help prevent or treat various disease risk factors including high blood pressure, high cholesterol, oxidative stress, hyperglycemia, and inflammatory activities. It is demonstrated that certain components of pomegranate such as polyphenols have potential antioxidant, anti-inflammatory, and anticarcinogenic effects. The antioxidant potential of pomegranate juice is more than that of red wine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(75 citation statements)
references
References 63 publications
(64 reference statements)
4
71
0
Order By: Relevance
“…Several studies have shown that due to phenolic compounds such as phenolic acid and flavonoids, pomegranates possess anti-oxidant (Heber et al, 2006), anti-carcinogenic (Khan, 2009), anti-inflammatory properties (Hollebeeck et al, 2012), as well as therapeutic efficacy (Jurenka, 2008;Zarfeshany et al, 2014). Studies investigating the protective effect of pomegranate against the nephrotoxic and hepatotoxic characteristics of cisplatin have examined that protection using materials prepared from pomegranate flower extract (Motamedi et al, 2014) and pomegranate seed extract (Ç ayır et al, 2011;Yildirim et al, 2013), have shown positive results.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that due to phenolic compounds such as phenolic acid and flavonoids, pomegranates possess anti-oxidant (Heber et al, 2006), anti-carcinogenic (Khan, 2009), anti-inflammatory properties (Hollebeeck et al, 2012), as well as therapeutic efficacy (Jurenka, 2008;Zarfeshany et al, 2014). Studies investigating the protective effect of pomegranate against the nephrotoxic and hepatotoxic characteristics of cisplatin have examined that protection using materials prepared from pomegranate flower extract (Motamedi et al, 2014) and pomegranate seed extract (Ç ayır et al, 2011;Yildirim et al, 2013), have shown positive results.…”
Section: Introductionmentioning
confidence: 99%
“…Native to the Middle East and North Africa, today pomegranate is spread globally due to its high longevity, drought and salinity resistance, and adaptability to different climatic conditions [2]. In particular, pomegranate is widely cultivated in Iran, India, China, USA, several countries of the former USSR, South Africa, and in Mediterranean countries such as Spain, Turkey, Egypt, Israel, To the best of our knowledge, no studies of the aqueous extracts of the Akko and Wonderful varieties of pomegranate as sources of anti-tyrosinase compounds have been conducted, and this is the object of our investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Pomegranate ( Punica granatum L.) juice (PJ) possesses anti-atherosclerotic, anti-cancer and antioxidant properties[20], and the antioxidant capacity of PJ surpasses those of red wine and green tea[21]. The bio-protective effects of PJ are due to the high content of a polyphenol, punicalagin.…”
Section: Introductionmentioning
confidence: 99%